Scapular kinematics in professional wheelchair tennis players. (March 2018) - Warner, Martin B.; Wilson, David; Heller, Markus O.; Wood, Dan; Worsley, Peter; Mottram, Sarah; Webborn, Nick; Veeger, DirkJan; Batt, Mark
Abstract: Background: Participating in wheelchair tennis increases the demands placed on the shoulder and could increase the risk of developing shoulder pain and injury that might be associated with differences in scapular kinematics. The aim of the study was to examine the presence of shoulder pain and scapular kinematics in professional wheelchair tennis players. Method: Scapular kinematics were obtained in 11 professional wheelchair tennis players, 16 people with shoulder impingement and 16 people without shoulder impingement during humeral elevation and lowering. Clinical examination of the wheelchair tennis players was undertaken using the Wheelchair Users Shoulder Disability Index (WUSPI) and clinical signs of shoulder impingement. Findings: The WUSPI questionnaire (mean = 28 SD 13.8) demonstrated wheelchair tennis participants experienced little shoulder pain and clinical examination revealed negative impingement tests. Wheelchair tennis players had greater scapular posterior tilt during humeral elevation (3.9° SE 1.71; P  = 0.048) and lowering (4.3° SE 1.8; P  = 0.04) on the dominant compared to non-dominant side. The dominant scapulae of wheelchair tennis players were significantly ( P  = 0.014) more upwardly rotated (21° SD 6.7) than the scapulae of people with shoulder impingement (14.1° SD 7.0) during scapular plane humeral elevation. Interpretation: This first study of scapular kinematics in professional wheelchair tennis athletes demonstrated bilateral asymmetries and differences to able-bodied participants with shoulder impingement. Understanding the role of sport participation on shoulder function in wheelchair users would assist in the development of preventative and treatment exercise programmes for wheelchair users at risk of shoulder injury and pain. Highlights: Absence of shoulder pain and impingement in professional wheelchair tennis players Bilateral asymmetry in scapular kinematics in wheelchair tennis players Differences in scapular kinematics to persons with and without shoulder impingement